Risk Factors of Vesicovaginal Fistula in Obstetrics - Nayab; Parveez, Khawaja Fawad; Mir, Komal (Indus Journal of Bioscience Research, 2025)
Background: Vesicovaginal Fistula is an obstetric complication that mainly affects women during the postpartum period in resource-poor areas worldwide. Fistulae lead to the leakage of urine into the vagina constantly, resulting in discomfort for the patient and creating feelings of shame for the sufferer. These include prolonged labor and operative delivery. Objective: To determine the frequency of obstetric risk factors associated with vesicovaginal fistula in women presenting to a tertiary care hospital. Study Design: Cross sectional study. Duration and Place of Study: This study was conducted from February 2025 to May 2025 in the Department of Obstetrics and Gynecology, Lady Reading Hospital, Peshawar. Methodology: A total of 121 women aged 18 to 40 years with vesicovaginal fistula were included. Risk factors including obstructed labour, C-section, and forceps delivery were assessed. Data analysis was done using Statistical Package for Social Sciences version 25. Association between risk factors and demographic variables was assessed using Chi square test and Fischer Exact test. A p-value ≤0.05 was considered significant. Results: The mean age was 28.12±6.66 years. Obstructed labour was the most common risk factor seen in 69.40% patients, followed by C-section in 33.10% and forceps delivery in 14.00%. No statistically significant association was found between demographic variables and risk factors (p>0.05). Conclusion: Obstructed labour remains the leading risk factor for vesicovaginal fistula.